2021
DOI: 10.3390/ijms22094509
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and Its Influence on the Bioactivities of a Novel Antimicrobial Peptide, Temporin-PF, and Its Analogues

Abstract: Temporin is an antimicrobial peptide (AMP) family discovered in the skin secretion of ranid frog that has become a promising alternative for conventional antibiotic therapy. Herein, a novel temporin peptide, Temporin-PF (TPF), was successfully identified from Pelophylax fukienensis. It exhibited potent activity against Gram-positive bacteria, but no effect on Gram-negative bacteria. Additionally, TPF exhibited aggregation effects in different solutions. Three analogs were further designed to study the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 60 publications
(88 reference statements)
1
24
0
Order By: Relevance
“…However, at higher peptide concentration, TLs are more likely to associate into dimers, which on the contrary lowers their antibacterial activity as indicated by the reduced geometrical defect size (or larger k shown in Figure 9D) and rare membrane pore formation. Previous studies have shown that aggregation of AMPs may lower their potency to disrupt the membrane and reduce their antibacterial efficacy [60][61][62]. For example, Zai et al recently showed that removal of Phe residue at N-terminus and substitution of Trp/D-Trp at C-terminus of a novel temporin peptide, Temporin-PF (FLPLIAGLFGKIF), resulted in an enhanced inter-peptide interaction in the zipper-like domain and eliminated their overall biological activities [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at higher peptide concentration, TLs are more likely to associate into dimers, which on the contrary lowers their antibacterial activity as indicated by the reduced geometrical defect size (or larger k shown in Figure 9D) and rare membrane pore formation. Previous studies have shown that aggregation of AMPs may lower their potency to disrupt the membrane and reduce their antibacterial efficacy [60][61][62]. For example, Zai et al recently showed that removal of Phe residue at N-terminus and substitution of Trp/D-Trp at C-terminus of a novel temporin peptide, Temporin-PF (FLPLIAGLFGKIF), resulted in an enhanced inter-peptide interaction in the zipper-like domain and eliminated their overall biological activities [62].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that aggregation of AMPs may lower their potency to disrupt the membrane and reduce their antibacterial efficacy [60][61][62]. For example, Zai et al recently showed that removal of Phe residue at N-terminus and substitution of Trp/D-Trp at C-terminus of a novel temporin peptide, Temporin-PF (FLPLIAGLFGKIF), resulted in an enhanced inter-peptide interaction in the zipper-like domain and eliminated their overall biological activities [62]. This implies that hydrophobicity and aggregation level of AMPs must be balanced to achieve maximum antimicrobial efficacy.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Likewise, temporin-PF identified from Pelophylax fukienensis displayed antimicrobial activity against MRSA (NCTC 12493), while it was ineffective against Gram-negative strains, such as Escherichia coli (NCTC 10418), P. aeruginosa (ATCC 27853), and K. pneumoniae (ATCC 43816), at a concentration of up to 128 μM. 36 However, Saha-CATH5 also exhibited a strong bactericidal activity against MRSA with a MIC of 32 μg/mL, while a concentration of 64 μg/mL had no effect against P. aeruginosa (ATCC 27853). 35 …”
Section: Resultsmentioning
confidence: 99%
“…Several studies mentioned that temporins were able to exhibit greater potencies against Gram-positive bacteria, such as S. aureus as compared to Gram-negative bacteria. ,, Moreover, temporin-SHd and Tasmanian devil cathelicidin Saha-CATH5 were ranked as the second and third potential anti-MRSA peptides, respectively. Temporin-SHd in the frog skin of Pelophylax saharicus was highly active against MRSA (ATCC 43300 and ATCC BAA-44) with a minimal inhibitory concentration (MIC) of 6.25 μM .…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the increase of hydrophobicity which resulted from the accumulation of a hydrophobic amino acid contributed to the aggregation between peptide molecules [ 54 , 55 ]. Too strong an aggregation ability may result in the premature aggregation of the peptide before they are attached to the cell membrane [ 56 , 57 , 58 ]. This can explain the decrease on the permeability and antibiofilm ability at high concentrations of T1CEh-KKPWW2 ( Figure 7 and Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%